Efectos persistentes de los experimentos aleatorios sobre desarrollo en Kenia (2020)
In recent years there has been a growing interest in the benefits of implementing randomised controlled trials (RCTs). However, although the attention provoked by RCTs has spread around the world, the implementation of these randomised trials has been focused on South Asia and East Africa. In particular, western Kenya has been the subject of multiple RCTs since before the popularisation of randomised experiments. Thus, this text seeks to identify whether the large amount of controlled research implemented in the western counties of Kenya has impacted the GDP of these regions. The number of families involved in RCTs per county is obtained from the databases of three institutions focused on the collection of information derived from randomized experiments. Indeed, OLS estimates suggest a correlation between GDP growth and the number of households involved in randomized trials...